The wage-price pass-through across sectors: Evidence from the euro area - Miguel Ampudia; Marco Lombardi; Théodore Renault (European Central Bank (ECB), 2024)
This paper studies the pass-through from wages to producer prices using sectoral disaggregated data for the euro area. We find a positive and statistically significant wage-price pass-through that reaches 50% after three years, which differs across sectors. The wage-price pass-through in private services is significantly higher than in industry and takes longer before reaching its peak. While a higher labour intensity is a key component of the pass-through, our estimates indicate that differences in sectoral labour shares alone cannot explain the larger wage-price pass-through in private services compared to industry. Instead, the estimates hint at an important role for international competition in the domestic market for the tradeable sector. They also suggest that the sales destination matters: wage growth contributes to domestic inflation for goods but not to export inflation. Finally, we also provide evidence of an increase in the wage-price pass-through after 2020, particularly in private services.
Keywords: E24; E31; 330; inflation dynamics; wage-price pass-through; sectors; international competition